New Aggregation-Induced Delayed Fluorescence Luminogens With Through-Space Charge Transfer for Efficient Non-doped OLEDs - Zhang, Panpan; Zeng, Jiajie; Guo, Jingjing; Zhen, Shijie; Xiao, Biao; Wang, Zhiming; Zhao, Zujin; Tang, Ben Zhong (Frontiers in Chemistry, 2019)
In this work, two tailor-made luminogens comprising of electron donors (acridine and phenoxazine) and acceptor (triazine) bridged by the through-space conjugated hexaphenylbenzene (HPB) are synthesized and characterized. Their thermal stability, electrochemical behaviors, crystal and electronic structures, and photophysical properties are systematically investigated. The crystal and electronic structures reveal that the peripheral phenyls in HPB are closely aligned in a propeller-like fashion, rendering efficient through-space charge transfer between donor and electron moieties. These molecules display weak fluorescence with negligible delayed component in solutions but strong fluorescence with greatly increased delayed component upon aggregate formation, namely aggregation-induced delayed fluorescence (AIDF). Their neat films exhibit high photoluminescence quantum yields (PLQY), and prominent delayed fluorescence. The nondoped organic light-emitting diodes (OLEDs) based on these new luminogens exhibit excellent performance with maximum external quantum efficiency of 12.7% and very small efficiency roll-off of 2.7% at 1000 cd m−2. Designing AIDF molecules with through-space charge transfer could be a promising strategy to explore robust luminescent materials for efficient nondoped OLEDs.